EXPLORING INDONESIAN EFL STUDENTS’ PERCEPTIONS OF GEMINI AI IN DEVELOPING ENGLISH SPEAKING SKILLS - Nurilahiah, Silva; Hasim, Wahid; Dewi, Sinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores Indonesian EFL students’ perceptions of using Gemini AI in developing their English speaking skills. The rapid growth of generative artificial intelligence has introduced innovative opportunities for language learning, particularly in speaking practice. Gemini AI offers interactive conversation, pronunciation modeling, instant feedback, and flexible self-directed learning experiences. This research employed a qualitative descriptive design involving semi-structured interviews with Indonesian university students who actively used Gemini AI for speaking practice. The findings indicate that students generally perceive Gemini AI positively due to its capacity to improve speaking fluency, pronunciation accuracy, vocabulary enrichment, and confidence. Participants reported that Gemini AI created a psychologically safe learning environment where they could practice without fear of social judgment. Additionally, the platform’s accessibility and flexibility encouraged autonomous learning. However, technical issues such as unstable internet connections and occasional unnatural conversational responses were identified as notable limitations. Overall, Gemini AI is perceived as an effective supplementary tool that supports both linguistic and psychological dimensions of English speaking development among Indonesian EFL learners.